Odpowiedź :
Odpowiedź:
a) 7a - 5 = 12 - a
7a + a = 12 + 5
8a = 17
a = [tex]\frac{17}{8}[/tex] = 2[tex]\frac{1}{8}[/tex]
b) -2x - 11 = 4 - 6x
-2x + 6x = 4 + 11
4x = 15
x = [tex]\frac{15}{4}[/tex] = 3[tex]\frac{3}{4}[/tex]
c) 5(x + 4) - (-2x + 1) = 4x + 3
5x + 20 + 2x - 1 = 4x + 3
7x - 4x = 3 + 1 - 20
3x = -16
x = -[tex]\frac{16}{3}[/tex] = -5[tex]\frac{1}{3}[/tex]
d) -2(2x + 3) + 5(x - 4) = 7
-4x - 6 + 5x - 20 = 7
x = 7 + 20 + 6
x = 33
e) [tex]\frac{2x}{7}[/tex] + [tex]\frac{1}{2}[/tex] = [tex]\frac{x}{14}[/tex] + 2 |×14
4x + 7 = x + 28
4x - x = 28 - 7
3x = 21
x = 7
f) [tex]\frac{x}{2}[/tex] + [tex]\frac{2}{3}[/tex] - [tex]\frac{2x}{3}[/tex] = [tex]\frac{5}{6}[/tex] |×6
3x + 4 - 4x = 5
-x = 5 - 4
-x = 1
x = -1
g) 0,7x - 1,2 = 6,5 + x
0,7x - x = 6,5 + 1,2
-0,3x = 7,7
x = -[tex]\frac{7,7}{0,3}[/tex] = -[tex]\frac{77}{3}[/tex] = -25[tex]\frac{2}{3}[/tex]
h) 6,2(3x - 1) + 1,4x = 2,2
18,6x - 6,2 + 1,4x = 2,2
20x = 2,2 + 6,2
20x = 8,4
x = [tex]\frac{8,4}{20}[/tex] = [tex]\frac{84}{200}[/tex] = [tex]\frac{42}{100}[/tex] = [tex]\frac{21}{50}[/tex]
i) [tex]\frac{x+1}{5}[/tex] + [tex]\frac{2x-3}{2}[/tex] = 0,7
[tex]\frac{x+1}{5}[/tex] + [tex]\frac{2x-3}{2}[/tex] = [tex]\frac{7}{10}[/tex] |×10
2(x + 1) + 5(2x - 3) = 7
2x + 2 + 10x - 15 = 7
12x = 7 + 15 - 2
12x = 20
x = [tex]\frac{20}{12}[/tex] = [tex]\frac{10}{6}[/tex] = [tex]\frac{5}{3}[/tex] = 1[tex]\frac{2}{3}[/tex]
j) [tex]\frac{3x-5}{3}[/tex] - [tex]\frac{x+1}{2}[/tex] = [tex]\frac{x-4}{6}[/tex] |×6
2(3x - 5) - 3(x + 1) = x - 4
6x - 10 - 3x - 3 = x - 4
3x - x = - 4 + 3 + 10
2x = 9
x = [tex]\frac{9}{2}[/tex] = 4[tex]\frac{1}{2}[/tex]